Prostate cancer post-prostatectomy radiotherapy: CT vs MRI for vesico-urethral anastomosis target delineation. Issue 1 (October 2017) - Lim Joon, Daryl; Lim, Adeline; Schneider, Michal; Hiew, Chee-Yan; Lawrentschuk, Nathan; Sengupta, Shomik; Foroudi, Farshad; Jenkins, Trish; Angus, David; Wada, Morikatsu; Chao, Michael; Khoo, Vincent
Abstract: Background: Vesico-urethral anastomosis (VUA) is critical to the clinical target volume (CTV) in post-prostatectomy radiotherapy (PPRT), as it is the commonest site of recurrence. Typically, this is performed on a CT alone but guidelines recommend MRI. Objective: To evaluate the VUA spatial differences between CT (ctVUA) and MRI (mrVUA) and analyse its impact on the CT defined CTV (ctCTV) as recommended by published guidelines. Materials and methods: We identified 34 patients with a co-registered simulation CT and T2 weighted MRI. The VUA was located on CT and MRI whilst blinded to the opposing scan. The differences were analysed using Wilcoxon's Signed Rank Test. The mrVUA coverage was investigated using three ctCTV margins of 5 mm, 8 mm and 12 mm. Results: Median age was 63 years with 59% having pT3a disease and median Gleason score of 7. The mrVUA was coincident with the ctVUA in 12% and inferior in 88%. Median difference was 5 mm (0–10 mm) ( P  < 0.0001). Only a ctCTV margin of 12 mm would have encompassed all mrVUAs. A ctCTV margin of 8 mm and 5 mm resulted in 12% and 38% cases where the VUA was excluded from the ctCTV. Conclusions: MRI is important for the accurate delineation of VUA for PPRT.